Ten lectures on cognitive sociolinguistics - Geeraerts, Dirk, 1955- (Distinguished Lectures in Cognitive Linguistics Ser., 2018)
Cognitive Sociolinguistics combines the interest in meaning of Cognitive Linguistics with the interest in social variation of sociolinguistics, converging on two domains of enquiry: variation of meaning, and the meaning of variation. These Ten Lectures, a transcribed version of talks given by professor Geeraerts in 2009 at Beihang University in Beijing, introduce and illustrate both dimensions. The 'variation of meaning' perspective involves looking at types of semantic and categorial variation, at the role of social and cultural factors in semantic variation and change, and at the interplay of stereotypes, prototypes and norms. The 'meaning of variation' perspective involves looking at the way in which categorization processes of the type studied by Cognitive Linguistics shape how scholars and laymen think about language variation.